A Recipe for Success: The Role of Supportive and Bureaucratic Organizational Cultures: Mediating the Relationship Between Service Quality and Customer Satisfaction in Online Food Delivery - Asghar, Umair; Ullah, Naqeeb; Ahmed, Ammar; Iftikhar, Danish (2024)
In this era of growing e-commerce businesses and the ever-increasing need for home delivery of food, this study investigates the factors influencing customer satisfaction in the online food delivery sector. It also focuses on the mediating variables of bureaucratic and supporting organizational cultures. From Lahore, Pakistan, a purposive sampling method was used to select 284 participants, and data was collected through structured questionnaires. The research underscores the importance of service quality in enhancing customer satisfaction, consistent with previous studies. The findings suggest that bureaucratic organizational culture was not a significant mediating factor, but the results expose its deficiencies. On the other hand, supportive organizational culture is only partially mediated, emphasizing the importance of building supportive cultures in organizations. This study also provides implications for online home delivery service providers to adopt consumer-oriented initiatives, foster supportive environments, and alleviate bureaucratic limitations in fulfilling customer satisfaction in this dynamic, growing industry.